Effectiveness of an Instructional Program Concerning premarital screening of sexual transmitted disease on Student's Knowledge at Baghdad University - Salman, Aqdas; abbas, Iqbal (Iraqi National Journal of Nursing Specialties, 2019)
Objectives: To identify the effectiveness of instructional program concerning premarital screening of sexual transmitted disease on student's knowledge at Baghdad University and examine the relationship between students' knowledge and certain studied variables. And hypothesis for this study; There is a difference in university student’s knowledge toward premarital screening between pre and posttests of instructional program. Methodology: A quasi-experimental design (pretest-posttest approach) was conducted at six colleges and its college of education ibn rushd, college of political science, college of law, college of literature, college of media and college of language. This study was conducted during the period of 1st April 2017 to 5th May 2018. Multistage stratified random sample of (40) students for both group control and study group at Baghdad University colleges. A questionnaire, was used as a tool of data collection. The questionnaire and content validity was carried out through the seven experts. Descriptive and inferential statistical analyses were used to analyze the data. Results: in general the results show a statistical significant improvement of university student's knowledge concerning premarital screening of sexual transmitted diseases Recommendations: Conducting frequent health education programs about PMS among students in high schools and universities to improve their knowledge toward sexual transmitted diseases